CHARACTERIZATION OF BIDIRECTIONAL TRANSMISSIVE AND REFLECTIVE PROPERTIES OF BLACK SILICON. Issue 1 (January 2022) - Georgiev, Georgi T.; Butler, James J.; Shiri, Ron; Jhabvala, Christine A.
Abstract: This paper describes the initial work of characterizing the transmissive and reflective properties of black silicon diffusers. The diffusers were fabricated from a 100 mm diameter black silicon sample at NASA's Goddard Space Flight Center (GSFC). The directional hemispherical reflectance from 250 nm to 2500 nm and BRDF/BTDF measurements at 632.8 nm, 1064 nm, and 1550 nm were measured using the GSFC Diffuser Calibration Laboratory's (DCL) spectrophotometer and optical scatterometer. The diffusers exhibit a low level of specular reflection up to 1100 nm with no evidence of retroscatter. The measurements are traceable to those made at the National Institute of Standards and Technology (NIST).